Preface to the Special Issue on “Quantum Computing Algorithms and Computational Complexity” - Pelayo, Fernando L.; Mezzini, Mauro (Mathematics (Basel), 2022)
In 1982, Richard Feynman stated that in order to simulate quantum systems, we would rather go for a sort of brand-new powered quantum processor instead of a classical one [...]